Changes In Biochemical And Cytokine Markers Of The Liver In The Acute Period Of Combined Facial Trauma (Texas Journal of Medical Science, 2026)
This article presents the results of an assessment of the functional state of the liver in patients with concomitant facial bone injuries. The study included 58 patients treated at the Andijan branch of the Russian Scientific Center for Emergency Medicine. Blood biochemical parameters reflecting inflammatory activity, protein-synthetic function of the liver, and the degree of cytolysis ( procalcitonin , total protein, albumin, ALT , and AST ) were assessed dynamically from admission to the seventh day. It was found that in the first hours after injury, a pronounced activation of the systemic inflammatory response and cytolytic syndrome is observed: a significant increase in procalcitonin , increased transaminase activity, and a decrease in protein fractions. By the fifth and seventh days, these parameters gradually normalize, indicating the restoration of metabolic liver function and the effectiveness of the therapy